Update on the use of pramipexole in the treatment of Parkinson’s disease - Radu Constantinescu (Dove Medical Press, 2008)
Radu ConstantinescuDepartment of Neurology, Sahlgrenska University Hospital, 413 45 Göteborg, SwedenAbstract: Pramipexole is a non-ergot dopamine agonist shown to be efficacious in the treatment of Parkinson’s disease (PD). This review addresses the literature concerning pramipexole’s efficacy in treating motor and non-motor symptoms in PD, its impact on the development of dyskinesias and response fluctuations, the issue of neuroprotection, and the risk for developing adverse events such as increased somnolence, attacks of sudden onset of sleep, cardiac valvulopathy and impulse control disturbances.Keywords: pramipexole, Parkinson’s disease, efficacy, adverse events